ANALISIS BUKU GURU SMP KELAS VIII PADA MATERI SISTEM ORGAN BERDASARKAN KOMPONEN PEDAGOGICAL CONTENT KNOWLEDGE - Mia Husniati Maulidya; Aa Juhanda; Gina Nuranti (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2020)
Pedagogical Content Knowledge (PCK) is knowledge of the material and how to teach it. The teacher uses the textbook as a reference when implementing the learning process. Therefore, the teacher's book must conform to the PCK component. The purpose of this study was to study the percentage of PCK components in the teacher's book. The research method used in this research is descriptive method with the subject of research by selecting chapters that enter the organ system, namely the human digestive system, human blood circulation system, human respiratory system and human excretion system. Based on the results of research that has been analyzed shows the emergence of PCK components in the teacher's book related to the 24.8% Natural Science meeting, the knowledge of the Natural Sciences curriculum 46.3%, the knowledge of 53.6% student understanding and the knowledge of the 54% Natural Science learning strategies.